3D-printed polylactic acid (PLA)/polymethyl silsesquioxane (PMSQ)-based scaffolds coated with vitamin E microparticles for the application of wound healing - ULAĞ, SONGÜL; GÜNDÜZ, OĞUZHAN (My University, 2024)
Skin is part of the integumentary and excretory system, which helps protect the body against infections. The skin should be properly treated when it gets injured, which requires a long healing process. In this study, 15% (w/v) polylactic acid (PLA) and 1 and 2% (w/v) polymethylsilsesquioxane (PMSQ) scafolds were fabricated using 3D printing technology, and the surfaces of each scafold were coated with 5% ethylcellulose (EC)/vitamin E microparticles using the electrospray method. The morphologies of the scafolds were characterized using a scanning electron microscope (SEM), and results showed that the pore sizes of the scafolds ranged from 136 to 265μm. The vitamin E was completely released from the scafolds within 5h. MTT test was performed with fbroblast cells and results proved the biocompatibility of the scafolds. These fndings showed that the scafolds may have good potential as a wound dressing material. The biodegradation test was performed in invitro conditions and results showed that the surface coating with 5% EC/vitamin E microparticles on the 15% PLA/2% PMSQ scafolds increased the degradation rate of the scafolds.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); Electrospray; Microparticles; PLA; PMSQ; Vitamin E; Wound healing; 3D printing